2D Node-Based Finite Element Method on Linear Accelerator Cavity for Radiation Therapy - Pusuluri, Vinod Babu; Prasad, A M; Darimireddy, Naresh K (International Journal of Membrane Science and Technology, 2023)
This paper deals with the Electromagnetic (EM) field characterization of an S-band Linear Accelerator (LA) Cavity, which is extensively used in cancer treatment. The analysis of the proposed cavity is carried out using an Eigen-mode full-wave EM solver. Mathematical formulation of cavity parameters using the Finite Element Method up to the system of equations is presented. The EM formulization uses a simple 2D square box as segmentation element and also node-based basis functions are used inside the cavity than the edge-based functions. The proposed numerical analysis of a single cavity of LA system is also applicable for a system with multiple numbers of cavities. The cavity has a resonance of 3.0474 GHz and a Q-factor of 17181.6 with finite conducting boundaries at the ends of the drift tube. The nose cone structure in the cavity is essential to have a stronger E-field at the center where the beam passes. Further, the particle acceleration is not constant along the axis of the cavity, which may have severe consequences for beam dynamics. Proper beam dynamics in LA plays a key role in reducing the mortality rate in cancer therapy applications.